Prognostic impact of epileptic seizures in multiple sclerosis varies according to time of occurrence and etiology. (25th September 2022) - Selton, Marion; Mathey, Guillaume; Soudant, Marc; Manceau, Philippe; Anxionnat, René; Debouverie, Marc; Jonas, Jacques
Abstract: Background and purpose: Epileptic seizures occur more often in patients with multiple sclerosis (MS) than in the general population. Their association with the prognosis of MS remains unclear. This study was undertaken to evaluate whether epileptic seizures may be a prognostic marker of MS disability, according to when the seizure occurs and its cause. Methods: Data were extracted from a population‐based registry of MS in Lorraine, France. Kaplan–Meier curves and log‐rank tests were used to compare the probability of different levels of irreversible handicap during the course of MS in patients who experience epileptic seizures or do not, according to the chronology and the cause of the first epileptic seizure. Results: Among 6238 patients, 134 had experienced at least one epileptic seizure (2.1%), and 82 (1.2%) had seizures secondary to MS. Patients with epileptic seizure as a first symptom of MS (14 patients) had the same disease progression as other relapsing–remitting MS patients. Patients who developed epileptic seizures during the course of MS (68 patients) had a higher probability of reaching Expanded Disability Status Scale = 3.0 ( p = 0.006), 6.0 ( p = 0.003), and 7.0 ( p = 0.004) than patients without an epileptic background. Patients with a history of epileptic seizures unrelated to MS also had a worse prognosis than patients without an epileptic background. Conclusions: Epileptic seizures might be viewed as a "classic MS relapse" in terms of prognosis if occurring early in MS, or as a marker of MS severity if developing during the disease. Epileptic diseases other than MS may worsen the course of MS.